Guanine Deaminase Stimulates Ultraviolet-induced Keratinocyte Senescence in Seborrhoeic Keratosis via Guanine Metabolites - Kyung Ah Cheong; Ai-Young Lee (Medical Journals Sweden, 2020)
DNA damage and oxidative stress play a critical role in photoageing. Seborrhoeic keratosis (SK) affects sunlight-exposed sites in aged individuals. This study examined the mechanism of photoageing in SK. The guanine deaminase gene, which is involved in purine metabolism, was upregulated with uric acid levels and p21 in SK. Guanine deaminase was detectable in keratinocytes. Repeated exposure to ultraviolet (UV) increased levels of guanine deaminase, together with DNA damage, such as γ-H2AX and cyclobutane pyrimidine dimer formation, generation of reactive oxygen species, and keratinocyte senescence, which were reversed by guanine deaminase knockdown. However, guanine deaminase overexpression and H2O2 formed γ-H2AX, but not cyclobutane pyrimidine dimer. Loss-of-function guanine deaminase mutants reduced the metabolic end-product uric acid, which was increased by exposure to exogenous xanthine. Repeated exposure to UV increased levels of uric acid. Exogenous uric acid increased cellular senescence, reactive oxygen species, and γ-H2AX, similar to guanine deaminase. Overall, guanine deaminase upregulation increased UV-induced keratinocyte senescence in SK, via uric acid mediated by reactive oxygen species followed by DNA damage.